Analysis Model of Online Task Based Language Teaching in English Skill Teaching at Man 1 Parepare - Nasli P; Zulfah Fakhruddin; Arqam; Abd Haris Sunubi; Ambo Dalle (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research aim to analysis Model of Online Task Based Language Teaching (OTBLT) in English Skill Teaching at MAN 1 Parepare. Method of research used descriptive qualitative, the informant of this research was English Teacher and the observation conducted at MAN 1 Parepare. The technique of analysis data was data reduction, displaying and drawn conclusion. The Result of study was 1) The Model of Online Task Based Language Teaching (OTBLT) in teaching reading at MAN 1 Parepare optimized online platforms which diverse reading materials and collaborative tasks to enhance students' reading skills which improve reading comprehension conducted from internet and media sources related to the students’ real-life situation. 2) The Model of Online Task Based Language Teaching (OTBLT) in teaching Speaking at MAN 1 Parepare prioritizes the development of speaking skills through various strategies which students are assigned speaking tasks that reflect real-situation communication such as buyer-seller interactions or dialogues between family members and students encouraged to find speaking texts in their own task for collaborative speaking activities at classroom related to the real situation. 3) The Model of Online Task Based Language Teaching (OTBLT) in teaching writing at MAN 1 Parepare providing students with engaging and meaningful writing experiences from many sources while students freely to get any writing text including descriptive writing and procedural texts related to the real situation. 4) The Model of Online Task Based Language Teaching (OTBLT) in teaching Listening at MAN 1 Parepare faces challenges in conducted specific listening task because listening task must optimized certain audio which hard to be implemented in Online Task Based Language Teaching (OTBLT) which related to the real situation of the students